Pengaruh Produk, Promosi, dan Pelayanan terhadap Keputusan Penggunaan Jasa Koperasi Simpan Pinjam Jasa Batang - Novalia Jaya Putri; Apriatni Endang Prihatini; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2022)
Kospin Jasa is one of the largest savings and loan cooperatives in Indonesia. In 2020 the assets of Kospin Jasa reached Rp9.6 trillion with the number of members in Indonesia reaching 334.092 customers, while the number of members at the Batang Branch Office was 2.222 customers. According to data, the number of members of Kospin Jasa shows a decrease in the number of members every year. This study aims to determine the effect of products, promotions, and services on decisions to use Kospin Jasa Batang services. This type of research is explanatory research. The sampling method in this research is probability sampling with simple random sampling technique and sampling frame. Data collection techniques used questionnaires and interviews with 96 respondents, members of Kospin Jasa Batang. The data analysis method used is regression analysis using the SPSS 26.0 application. The results showed that products, promotions, and services had an effect on purchasing decisions. There are suggestions given to Kospin Jasa based on each aspect, including on product aspects, it is necessary to improve product quality such as improving interest rates on each product and increasing the opening of deposits and loans to be easier. In the promotion aspect, it is necessary to increase the diversity of advertising media so that it is more easily known by the public and increase the knowledge of officers in providing accurate and clear information either to customers or prospective customers. In the service aspect, Kospin Jasa officers need to prioritize the interests of customers, respond to anyone who submits complaints, be able to know, understand, and answer all complaints, and be responsive in providing services and service processes so that customers are satisfied with the services provided by Kospin Jasa, so that creating customer loyalty to Kospin Jasa.